2010
DOI: 10.1097/brs.0b013e3181c176f8
|View full text |Cite
|
Sign up to set email alerts
|

Transpedicular Grafting After Short-Segment Pedicle Instrumentation for Thoracolumbar Burst Fracture

Abstract: Additional TPCB grafting after posterior short-segment instrumentation remains a reliable surgical method for correcting and maintaining sagittal alignment and vertebral body height in thoracolumbar burst fractures. Calcium sulfate cement also proved to be an effective bone substitute used in spinal surgeries for patients with thoracolumbar burst fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…These range from modifications of the system of fixation with the addition of a cross-connector or an extra screw at the fracture site, to procedures aimed at reducing the bone loss in the anterior column by transpedicular augmentation of the fractured vertebra, or kyphoplasty. Opinion about the role of transpedicular augmentation of the fractured vertebra remains divided: Alanay et al 20 reported no benefit, whereas Liao et al 24,25 reported an improved outcome. Augmenting the anterior column by introducing cement has been shown to be of value in preventing collapse of the fractured vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…These range from modifications of the system of fixation with the addition of a cross-connector or an extra screw at the fracture site, to procedures aimed at reducing the bone loss in the anterior column by transpedicular augmentation of the fractured vertebra, or kyphoplasty. Opinion about the role of transpedicular augmentation of the fractured vertebra remains divided: Alanay et al 20 reported no benefit, whereas Liao et al 24,25 reported an improved outcome. Augmenting the anterior column by introducing cement has been shown to be of value in preventing collapse of the fractured vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines based on the level 1 studies of when and how the anterior column should be additionally reconstructed surgically do not exist up to date [10,19,21,36,[53][54][55][56]59]. 360°fusions are considered to be necessary in cases with ''unstable'' burst fractures and more severe bony destruction [5, 11, 25, 26, 28, 31-33, 45, 47, 53, 58].…”
Section: Introductionmentioning
confidence: 99%
“…Successful outcomes have been documented with the usage of polymethylmethacrylate (PMMA), hydroxyapatite (HA) and calcium sulphate (CS) 5 . Despite good early results, PMMA, HA and CS can never replace autogenous cancellous bone graft in their ability to provide the best bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recent encouraging results 1,2 , there are -doubts about the efficacy of the transpedicular bone grafting techniques which have led to failures in maintaining the reduction and complications of internal fixation 3,4 . However, the usage of bone graft substitutes which are radio-opaque to augment the anterior column have been reported to be successful 5 . Therefore, we postulate that the previous failures in transpedicular bone grafting may be due to the lack of clear visualization of bone grafts inserted.…”
Section: Introductionmentioning
confidence: 99%